Contributions of Nursing Preceptorship in the context of Primary Health Care from the perspective of active methodologies (Research, Society and Development, 2020)
Objective: to analyze the activities of nursing preceptorship in the context of Primary Health Care from the perspective of active methodologies. Methodology: a descriptive study with a qualitative approach, carried out with 11 nurse preceptors who work in Primary Health Care units, in which semi-structured interviews were adopted for data production and thematic analysis was applied. Results: thematic axes were produced that enabled the formulation of three categories: Nursing preceptorship and the adoption of active methodologies in Primary Health Care; activities considered as active methodologies; unraveling the difficulties in adopting the active methodology in Nursing preceptorship. Discussion: it was found that the adoption of active methodologies by preceptors in practice scenarios contributes to a differentiated and qualified training of professionals to work in the Primary Health Care scenario. Active methodologies are being widely adopted by preceptors; and among the strategies most used by preceptors, are the case study, problem-based learning, role play and one-minute preceptorship. Some obstacles were presented, such as work overload, lack of knowledge about active methodologies and little knowledge of management and other professionals in the work of preceptors. Conclusion: the adoption of active methodologies by nurses who exercise the role of preceptor is of great importance in active learning, becoming essential to stimulate learning, thus favoring the formation of critical and reflective professionals.